Music therapy in strengthening the psychological well-being of military police officers (Research, Society and Development, 2025)
Music therapy is a therapeutic practice that uses music as a tool to promote mental health and psychological well-being. In the police-military context, marked by a high emotional load and a demand for behavioral control, it becomes essential to adopt strategies that minimize occupational stress and promote the emotional balance of professionals. The general objective of this study was to demonstrate the effects of music therapy on strengthening the psychological well-being of military police officers. This is an experience report developed by nursing students during an extension activity in a battalion of the Military Police of Amazonas, involving a live musical intervention with direct observation of the participants' reactions. The results revealed an improvement in the organizational climate, greater interaction among colleagues, and a feeling of relaxation and tranquility. It is concluded that music therapy represents a humanizing, preventive, and effective tool in promoting mental health in environments of high emotional pressure.